2003
DOI: 10.1016/s0022-5223(02)73241-8
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery patency and clinical outcomes: five-year interim results of a randomized trial

Abstract: The 5-year interim results do not support the hypothesis that the radial artery has superior patency to or is associated with fewer clinical events than free right internal thoracic artery or saphenous vein grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(123 citation statements)
references
References 38 publications
3
116
0
4
Order By: Relevance
“…5,6 ). Although, a number of observational studies have demonstrated the superiority of RA in terms of better patency and clinical outcome, randomized trials suggested only better angiographic results of RA in 1-year and 5-year follow-up with no difference in clinical outcome [5][6][7][8][9][10][11] . Moreover, dealing with less tight coronary lesions (<80%), particularly in the right coronary artery territory, and with the group of patients 70+, use of RA did not carry any benefit of importance over GSV (ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 ). Although, a number of observational studies have demonstrated the superiority of RA in terms of better patency and clinical outcome, randomized trials suggested only better angiographic results of RA in 1-year and 5-year follow-up with no difference in clinical outcome [5][6][7][8][9][10][11] . Moreover, dealing with less tight coronary lesions (<80%), particularly in the right coronary artery territory, and with the group of patients 70+, use of RA did not carry any benefit of importance over GSV (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dealing with less tight coronary lesions (<80%), particularly in the right coronary artery territory, and with the group of patients 70+, use of RA did not carry any benefit of importance over GSV (ref. 10,11 ). RA harvesting performed through an uninterrupted incision in Reyes's modification is simple, quick, and safe No.…”
Section: Discussionmentioning
confidence: 99%
“…The other randomized controlled clinical trial was performed by Buxton et al [31] in 2003. These authors recruited 438 patients who were randomized in two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Category D were excluded from this systematic review. Two studies were classified in Category A (Dessai et al, 2004; Buxton et al, 2003) [29,30] and one study was classified as Category B (Muneretto et al, 2004) [31].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…The Radial Artery Patency and Clinical Outcome (RAPCO) study, was undertaken to compare angiographic patency and cardiac-event-free survival of the RA graft with that of the free RITA and SV during a 10-year period after CABG [55].…”
Section: The Radial Artery (Ra)mentioning
confidence: 99%